Subungual melanoma in the practice of surgeon and oncologist - M. Y. Myasnyankin; G. I. Gafton; V. V. Anisimov (Амбулаторная хирургия, 2017)
Subungual melanoma is a rare malignancy of which practitioners in various fields including oncologists know little; the work, therefore, is of great practical importance, since it could improve the diagnosis of melanoma not only by oncologists, but also by surgeons, general practitioners, dermatologists and other specialists. The article provides full and detailed information on the clinical manifestations of subungual melanoma, especially in the early stages, recommends an algorithm for timely diagnosis, suggests the optimum volume of surgical treatment, outlines prognostic factors for this form of melanoma.